EXTERNAL ECONOMIC ACTIVITIES OF UZBEKISTAN: PROBLEMS AND SOLUTIONS - Saidova, Ogiloy (Ижтимоий-гуманитар фанларнинг долзарб муаммолари / Актуальные проблемы социально-гуманитарных наук / Actual Problems of Humanities and Social Sciences., 2020)
In this article international trade, external trade, import and export operations, the current situation are discussed. Figures from 2015 year to the first 4 months of 2020 year are analyzed in foreign economic activities in Uzbekistan.